International commercial and marine arbitration - Zekos, Georgios I. (Routledge-Cavendish research in international commercial law, 2008)
Analyses and compares commercial-martime arbitration, and the role of the courts in arbitration in several different legal systems including the US, the UK, Greece and Belgium, and also sets out how the process of arbitration should be developed in order to make it effective.